Digital image correlation applied to lime-based mortars: Shrinkage tests for durability evaluations in restoration works - Alessandro Grazzini; Giuseppe Lacidogna; Marco Zerbinatti; Sara Fasana; Federico Vecchio (Developments in the Built Environment, 2022)
Repair mortars applied to architectural heritage buildings for preservation, maintenance, restoration, and strengthening must be carefully studied regarding the many different compatibility issues. In the case of repair interventions, two closely related aspects are especially important: the mortar composition, and the method of its application, which can strongly influence the shrinkage phenomena during the setting and hardening phases. The aim of present experimental research is to set-up a procedure by Digital Imaging Correlation (DIC) technique to deepen shrinkage phenomena in lime-based mortars, thus comparing many different materials, wrongly considered to be similar in behaviour. The technique enable not only shrinkage measurement accuracy higher than standard tests, but also to understand its mechanisms of evolution over time, by evaluating locally strain stress before micro-crack appearing. The interpretation of a large number of test results represents a significant contribution to the development of operational tools to address material selection in specific contexts.